B3O3 monolayer: an emerging 2D material for CO2 capture. (4th August 2021) - Rahimi, Rezvan; Solimannejad, Mohammad
Abstract : The calculated CO2 capture capacity of the desired B3 O3 monolayer in the present study is high that it can be recognized as an emerging material for efficient CO2 capture. Abstract : In the current investigation, the CO2 capture capacity of the fabricated B3 O3 monolayer was assessed via a periodic DFT study. The present study results show that pristine B3 O3 nanosheets can take up five CO2 molecules with a CO2 capture capacity of 57.76 wt%. The average adsorption energy of adsorbed CO2 on the studied adsorbent falls in the range from −0.248 to −0.429 eV/CO2 . The calculated CO2 capture capacity of the desired B3 O3 monolayer in the present study is high; therefore, it can be recognized as an emerging material for efficient CO2 capture.